The Addition of Navigation Technology to the Femur-First Approach in Anterior Total Hip Arthroplasty Improves Leg Length Restoration - Stephanie V. Kaszuba, MD; Noah Gordon, BS; Alex C. Gordon, MD (Arthroplasty Today)
Background: The addition of computer navigation (CN) technology in direct anterior approach (DAA) total hip arthroplasty (THA) has the potential to improve restoration of hip offset and leg length. In this investigation, we examine the effect of one fluoroscopic-based CN system on biomechanical parameters in DAA THA with femur-first (FF) workflow. Methods: A retrospective review was performed on 235 primary DAA FF THA cases, with 100 CN cases and 135 in the conventional fluoroscopic overlay (FO) group. Radiographic examination was performed. Radiographic outcome measures included differences in hip center position, femoral offset, global offset, and leg length between the THA and native hips. Intraoperative and postoperative complications were also documented. Statistical analysis was performed using a t test for continuous data and a ꭓ2 test for categorical data. Results: While there were differences in individual components of femoral offset and the horizontal hip center, mean difference in global offset was not statistically different between the CN (mean: 2.15 mm) and FO (mean: 1.85 mm) groups (P = .898). The number of outliers was also statistically insignificant. The CN group demonstrated significant improvement in mean leg length discrepancy (mean: 1.52 mm) in comparison to the FO group (mean: 2.26 mm) (P = .001), with 1.09% and 8.89% of outliers, respectively (P = .013). Conclusions: The addition of CN technology to DAA FF THA improved the accuracy and precision of restoring leg length. CN did not significantly affect global offset. There was no significant difference in complications between the CN and FO groups.